Digital arbitration — A useful tool in the hands of homo sapiens - A. A. Kostin; A. V. Grebelsky (Цифровое право, 2021)
Currently, general digitalization has not spared the sphere of arbitration. What are the advantages and disadvantages of introducing digital technologies, how has COVID-19 influenced the work of leading arbitration institutions, does digitalization imply the delocalization of ICA, and does a “digital arbitrator” have a future? Alexey A. Kostin and Alexander V. Grebelsky answered these and other questions from Maxim I. Inozemtsev, Editor-in-Chief of the Digital Law Journal.